Humanized care at hospital emergency services according to companions - Andrade, Luciene Miranda de (2017)
Nowadays, health care humanization is a growing demand in the Brazilian context. However, in practice, it has not occurred, mainly in urgency and emergency care services. This study aimed to examine how companions perceive emergency care humanization at a public referral institution in Fortaleza-Ce/Brazil, in the second semester of 2006. Ten companions participated in data collection, at the end of each care session. The most important results were: lack of communication; high demand; infrastructure problem; professional commitment jeopardizing humanization in the client care process. It is concluded that, according to the companions, humanization can be achieved through small actions: watching attentively; sufficiently adequate environment, material and equipment, as the correct application of resources is a conditioning factor for humanization.